The gas structure of the HD 163296 planet-forming disk - gas gaps or not?. Issue Volume 15:Issue S350(2019) (April 2019) - Rab, C.; Muro-Arena, G. A.; Kamp, I.; Dominik, C.; Waters, L. B. F. M.; Thi, W-F.; Woitke, P.
Abstract: HD 163296 is a young star surrounded by a planet-forming disk that shows clear signatures of dust gaps and rings; likely an indication of ongoing planet formation. We use the radiation thermochemical disk code ProDiMo to investigate the impact of dust/gas gaps on the temperature, chemistry and observables. Furthermore, we model high spatial resolution gas and dust observation of HD 163296 (ALMA/DSHARP). Our first results indicate that features in the observed radial intensity profile of the 12 CO line are a consequence of the dust gaps and do not require gas depletion. Those preliminary results indicate that self-consistent modelling of the gas (chemistry, heating/cooling) and dust is necessary to accurately infer the degree of gas depletion within dust gaps. Such information is crucial to understand the processes that generate the disk substructure and their relation to planet formation.